Dynamic balance and ankle injury odds: a prospective study in 196 Dutch physical education teacher education students - Evert Verhagen; Sander Bliekendaal; Janine Stubbe (BMJ Open)
Objective The aim of this study was to investigate whether dynamic balance, measured with the anterior component of the Star Excursion Balance Test (SEBT-ANT), is a risk factor for ankle injuries in physical education teacher education (PETE) students.Design and setting A prospective monocentre study in first-year PETE students.Participants A total of 196 subjects, of which 137 men (70%) and 59 women (30%).Outcome measures This study consisted of measures of the SEBT-ANT at baseline (September 2015) and an injury registration procedure during a follow-up period (September 2015–June 2016). The association between the SEBT-ANT score and subsequent ankle injury was analysed with generalised estimating equations analysis at the leg level.Results Men and women had an average SEBT-ANT score of, respectively, 65.1% and 67.7% of leg length. In 20 (15%) subjects, the first injured body site involved the ankle. Across all participants, a below average SEBT-ANT score was not associated with increased ankle injury odds (OR OR=2.43, 95% CI: 0.94 to 6.29, p=0.07). In men, a below average SEBT-ANT score indicated sevenfold increased odds for ankle injury (OR=7.06, 95% CI: 1.43 to 34.92, p=0.02). In women, this relationship was not significant (OR=0.72, 95% CI: 0.19 to 2.71, p=0.62).Conclusions Below average normalised SEBT-ANT scores were associated with sevenfold likelihood for ankle injuries in men. In contrast, no relationship was found for the SEBT-ANT score and ankle injuries in woman. These results may provide directions for the implementation of screening tools, as part of an injury prevention programme, to identify male PETE students with an increased likelihood for ankle injuries.